Racial Swearing in Compliments on X: A Pragmatic Perspective - Putri, Aprilia Kartika; Triandana, Anggi; Fitriah, Siti; Putra, Yoga Mestika; Sirait, Jeliana Veronika (Puitika, 2024)
Abstract  Few realize that swearing is not always used to express negative emotions. It can also be utilized to convey positive feelings, such as compliments. Swearing in compliments is a phenomenon identified on X, the social media platform that was formerly known as Twitter. The purpose of this study is to examine the pragmatic meaning and the pragmatic function of racial swearing in compliments on X. This study is classified as descriptive qualitative research. The data of this study consisted of racial swearing in the compliment utterances on X. The observational method was used to gather the data. In the meantime, the data were analyzed using the identity method by referring to the theories of Hughes (2006), Kreidler (2002), Ljung (2011), and Spears (2000). The results of the data analysis are presented by using informal method. The study's findings demonstrate that the racial swearing in compliments on social media X has the pragmatic meaning of ‘guy’. In addition, it has pragmatic functions as noun supports and anaphoric use of epithets. As a noun support, the racial swearing was used to assist the compliment word, which was usually in the form of an adjective. On the other hand, as the anaphoric use of epithets, the racial swearing was used as an anaphoric pronoun, a pronoun that refers back to another noun in the utterance. It is anticipated that this study would lessen the misunderstanding that Indonesian EFL (English as a Foreign Language) students may have when interacting with other English speakers on social media X.